SOCIO-ECONOMIC AND ENVIRONMENTAL IMPACTS OF THE WATERSHED MANAGEMENT PROJECTS IN DAM CATCHMENT - Soleiman RASOULIAZAR; Saied Fealy NAHAVAND (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this descriptive-correlation study was to investigate socio-economic and environmental impacts of the watershed management projects in Mahabad’s dam catchment. The research instrument was structural questionnaire with close-ended questions which its validity and reliability was confirmed. The target population of this study consisted of all householders who lived in Mahabad’s dam catchment (N=2,458) out of which, according to Cochran’s formula, a number of 175 people were selected using cluster sampling in a simple randomization method (n=175). The descriptive results indicated the status of environmental, economic, and social impacts of watershed management in Mahabad’s dam catchment were at nearly high, nearly appropriate, nearly and low levels, respectively. These results also showed the main economic, environmental, and social impacts of watershed management were changing dry farming into irrigated farming, controlling flood, and attracting rural people’s participation, respectively. The results of Friedman test indicated environmental and social impacts were the most and the least amount of impacts of watershed management in Mahabad’s dam catchment, respectively. The results of correlation coefficient showed that there was the significantly positive relationship between land under cultivation and number of respondents’ household individual who participated in agricultural activities with impacts of watershed management in Mahabad’s dam catchment.